2003
DOI: 10.1002/jnr.10604
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and electrophysiological characterization of abnormal cell types in pediatric cortical dysplasia

Abstract: The mechanisms responsible for seizure generation in cortical dysplasia (CD) are unknown, but morphologically abnormal cells could contribute. We examined the passive and active membrane properties of cells from pediatric CD in vitro. Normal- and abnormal-appearing cells were identified morphologically by using infrared videomicroscopy and biocytin in slices from children with mild to severe CD. Electrophysiological properties were assessed with patch clamp recordings. Four groups of abnormal-appearing cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
185
3
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(204 citation statements)
references
References 53 publications
(69 reference statements)
14
185
3
2
Order By: Relevance
“…More o v e r, e l e c t rophysiological re c o rdings "in vitro" of dysplastic tissue from epileptic patients demonstrated that calcium currents and densities are greater in abnormal ("giant") compared with normal-appearing pyramidal neurons. These data support the idea that a b n o rmal or dysplastic neurons could play a role in the generation of epileptic activity in our patient 21 .…”
Section: Discussionsupporting
confidence: 91%
“…More o v e r, e l e c t rophysiological re c o rdings "in vitro" of dysplastic tissue from epileptic patients demonstrated that calcium currents and densities are greater in abnormal ("giant") compared with normal-appearing pyramidal neurons. These data support the idea that a b n o rmal or dysplastic neurons could play a role in the generation of epileptic activity in our patient 21 .…”
Section: Discussionsupporting
confidence: 91%
“…These studies have identified important mechanisms leading to specific neuroanatomical pathologies that interrupt normal stages of cortical development. However, seizures can also arise in human brain regions not classified as disorganized Major et al, 2009), and clear evidence for a population of "epileptic" dysplastic neurons has failed to emerge (Cepeda et al, 2003;George and Jacobs, 2011). Using an animal model of human lissencephaly, we show that functional integration of granule cells within the malformed DG is disrupted by LIS1 haploinsufficiency.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, acquired epilepsy models are often associated with enhanced proliferation of newborn granule cells (Parent et al, 1997;, but adult-born granule cell survival is reduced in LIS1 mutants . Because dysplastic neurons can also exhibit delayed synaptic maturation (Ackman et al, 2009) and sometimes fail to integrate into functional networks (Cepeda et al, 2003), the synaptic integration of adult-born granule cells might be different in epilepsies associated with an MCD. To address these issues, we used LIS1 mutant, enhanced green fluorescent protein (EGFP) reporter, and conditional knock-out mice in a series of immunohistochemical and electrophysiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…Mathern and co-workers (103,105,106; for review, see Ref. 104) have extensively investigated the properties of neurons in slices obtained after surgical interventions in migration disorders.…”
Section: Excitatory Gaba In Migration Disordersmentioning
confidence: 99%